Instant response to the novel virus: A bibliometric analysis of the incipient publications on COVID-19 - Lan, Rong; Jiang, Peiru; Wang, Yujun; Ye, Mengliang; Ou, Rong (Malaysian Journal of Library and Information Science, 2020)
The emergence of the novel coronavirus disease 2019 (COVID-19) is a serious global public health problem. The mystery around the causative agent was revealed on 7 January 2020 when the pathogen was isolated by Chinese scientists and named as novel coronavirus-2019 (2019-nCoV). With quicker reaction to the contagion, the number of scholarly research publications have increased exponentially, which calls for bibliometric analysis and review of the incipient studies. Therefore on 7 Feb 2020, the English language and Chinese publications on COVID-19 were retrieved from PubMed and CNKI (China National Knowledge Infrastructure). A retrospective bibliometric analysis was performed to gauge the output, language, document type, journal, authorship, geographical distribution, research focus, resulting in a total of 154 papers comprising 100 papers in English and another 54 in Chinese. There were 30 journals published at least 2 papers, and the Journal of Medical Virology published the most papers (11). China and USA were the most productive countries, and there were 24 international collaborative papers. Fudan University contributed the most papers. Isaac I. Bogoch, Kunling Shen, Xingguang LI, Hongzhou Lu were the most active authors as first authors, with 2 papers respectively. Among the 154 publications, 35 were opinions papers, and 30 were research articles. Papers were categorized by research areas, and five research foci were identified. Our study offers an overview of the incipient publications and quantitative information for future research on coronavirus. Besides, Chinese publications were also retrieved for an integrated data analysis and diversity comparison.